Analisis Pengelolaan Sampah di Tempat Pembuangan Sementara (TPS) Kelurahan Kedungsoko Kabupaten Tulungagung - Mayang Fatmawati; Erina Mifta Alvira; Muchamad Khasan Noto Raharjo; Hany Nur Pratiwi (Universitas Katolik Widya Karya Malang, 2023)
Garbage is defined as waste that has a solid form originating from human and animal activities that are not utilized. This study aims to find out how the waste management system is with the existence of a waste bank in the Kedungsoko Village, Tulungagung Regency. The research technique used is by means of observation, field surveys, interviews and literature studies. The result of this research is that waste management at the Temporary Disposal Site (TPS) of Kedungsoko Village is carried out properly through the Makmur Banksa Garbage Bank. The management stage is divided into the Waste Collection Stage, the Waste Processing Stage, and the Product Marketing Stage. Management constraints are limited tools so it is necessary to cooperate with partners. Overall management at the Makmur Banksa Garbage Bank is running effectively and is able to provide benefits to the surrounding community. The Makmur Banksa Garbage Bank can be used as a guideline for waste management for the community because of good and effective management.